Invitro evaluation of transdermal patch for edivoxetine hydrochloride - Ramakrishna Reddy Voggu,; Ravi Teja.Tumburu, (International Journal of Pharma and Bio Sciences, 2020)
The aim of this study was to create a transdermal patch of Edivoxetine hydrochloride which has an appreciable mechanical properties. The transdermal patches were prepared using solvent casting method . Various groups of patches with medication were prepared using diverse inclusion of polymers, for example, HPMC (different grades) ), Polyox303, Eudragit RL 100.Considering solubility of drug and polymer, the solvent system of water: ethanol was chosen. Invitro release of drug substance was performed using phosphate buffer (PBS) pH 7.4. Compatibility of drug with various excipients (drug: excipient in the proportion 1:1) was studied using Fourier Transform Infra-Red Spectroscopy (FTIR). Assessment test, weight variation, content uniformity, drug content, collapsing perseverance, thickness, invitro disintegration and invitro crumbling were completed. The folding endurance of all batches found less than 500 times . The rates of medication dispersion was found between 72 and 100%.The formulation F4 containing a combination of HPMC and Eudragit showed maximum drug release of 94.23%. The method employed to prepare patches was capable of producing patches with almost uniform drug distribution. Stability studies were conducted as per ICH guidlines (40±2â—‹C at 75±5% RH) for optimized formulations and was found to be stable.